2007
DOI: 10.1016/j.gene.2006.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PACT is regulated by Sp1 transcription factor

Abstract: PACT is a stress-modulated, cellular activator of interferon (IFN)-induced double-stranded (ds) RNA-activated protein kinase (PKR) and is an important regulator of PKR-dependent signaling pathways. The research presented here is aimed at understanding the regulation of PACT expression in mammalian cells. PACT is expressed ubiquitously in different cell types at varying abundance. We have characterized the sequence elements in PACT promoter region that are required for its expression. Using deletion analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 57 publications
1
3
0
1
Order By: Relevance
“…Sp1 is crucial for basal transcription of KLF5 , DRG2 and PRKRA . 24 , 25 , 26 We confirmed that TRA2β4 knockdown significantly increased the expression of these mRNAs in HCT116 cells, suggesting that interactions between TRA2β4 and Sp1 may be able to significantly alter the gene expression program.…”
Section: Discussionsupporting
confidence: 63%
“…Sp1 is crucial for basal transcription of KLF5 , DRG2 and PRKRA . 24 , 25 , 26 We confirmed that TRA2β4 knockdown significantly increased the expression of these mRNAs in HCT116 cells, suggesting that interactions between TRA2β4 and Sp1 may be able to significantly alter the gene expression program.…”
Section: Discussionsupporting
confidence: 63%
“…Induction of PACT expression upon Tunicamycin treatment was inhibited by actinomycin D, thus confirming that ER stress increases PACT expression at the mRNA level. The exact mechanisms triggering PACT gene expression remains to be determined, but it is already known that the expression of PACT is regulated by the SP1 transcription factor (12), and that ER stress pathways induced by tunicamycin or thaspigargin can activate SP transcription factors, including SP1 protein (1). It is not yet clear whether SP1 mRNA and protein levels are increased or not in AD brains (7, 29).…”
Section: Discussionmentioning
confidence: 99%
“…To verify that SP1 binds to the immediate upstream region of the CCL5 promoter in native chromatin, ChiP assay was used (40). SP1 Ab was used to immunoprecipitate the CCL5 promoter DNA from YT cells.…”
Section: Sp1 Binds In Vivo Near the Tata Box On The Ccl5 Promotermentioning
confidence: 99%